PERFORMANCE OF THE VASCULAR STIFFNESS INDICATORS AND THE PROCESS OF LEFT VENTRICLE REMODELING IN HYPERTENSIVE PATIENTS UNDER RENAL REPLACEMENT THERAPY - E. A. Praskurnichiy; I. E. Minyukhina (SINAPS LLC, 2019)
Objective. The objective of our study was to compare the performance of vascular stiffness (VS) and the left ventricular (LV) remodeling process indicators in patients with arterial hypertension (AH) under renal replacement therapy (RRT), and patients with essential hypertension.Design and methods. 158 people were included in the study, divided into 4 comparable age groups: 32 patients receiving programmed hemodialysis (PH), 37 recipients of renal transplant (RT), 69 patients with essential AH and 20 healthy volunteers. All the patients underwent 24-hour blood pressure (BP) monitoring with an assessment of VS and central BP (SBPao) and echocardiography (EchoCG).Results. The patients under PH and after RT did not have any significant differences in the values of central and peripheral BP. Comparing the groups of patients under RRT with the group of essential AH, the office systolic (SBP) and diastolic (DBP) BP values did not differ significantly. Аlthough, at night, considerably higher DBP(n) and SBPao(n) values were detected in patients under RRT, and in the patients after RT SBP(n) and PP(n) values were also increased. An increase in the SBPao values of more than 10 m/sec was detected only in the groups of patients under RRT. In all the groups with hypertension all indicators of daily VS differed significantly from the group of healthy volunteers. PTIN (Pulse Time Index of Norm) in the studied groups had more evident differences: in the healthy volunteers it was in the range of 80-90%, in the patients with essential hypertension - 50-60%, and in the patients under PH and after RT - 20-40%. In all groups of patients with AH, the average the posterior wall thickness (PWT) of the LV and the interventricular septum thickness (IVST) were close to the upper limit of the norm. In the groups of patients with AH an increase in the relative wall thickness (RWT) of the LV was also detected. Furthermore, considerably higher the values of ILVmass, IVST were found in the group of patients on PH in comparison with the patients after RT. In addition, in all the groups of patients with AH, there was a tendency to LV spherification in comparison with the healthy volunteers, and in the group of essential AH the difference was more pronounced compared with the group under RRT.Conclusion. In the patients with arterial hypertension who undergo renal replacement therapy, higher average values of central BP, higher vascular stiffness (daily pulse wave velocity in the aorta and a longer period of pulse wave velocity increase in the aorta during the day (PTIN)) and less pronounced left ventricular spherification are recorded in comparison with the patients with essential hypertension while office BP values remained consistent.